RESPONSE OF GROUNDNUT GENOTYPES TO HIGH AND LOW PHOSPHORUS LEVELS - B.C. AJAY*, A.L. SINGH, S.K. BERA, NARENDRA KUMAR, M.C. DAGLA; K.C. NATARAJ (The Journal of Research ANGRAU, 2019)
Groundnut production is often limited by low availability of soil phosphorus. Groundnut genotypes differ in their P efficiency and dry matter production under low P availability. Two Groundnut genotypes were used in this study namely ICG(FDRS)-10 (absorb and translocate large amount of P) and JL-24 (not suitable for P insufficient conditions) to study the response of P availability. Plants were grown in pots with two P levels viz. without P (0 mg P/kg soil, LP) and with P (40mg P/kg soil, HP) and parameters such as shoot length, root length, root volume, no. of lateral roots, nodules per plant, stem weight and leaf weight were recorded. Growth of groundnut genotypes was affected at 60 DAE i.e. during pegging stage. Low phosphorus (LP) resulted in reduced stem weight, leaf weight, shoot length and root volume, nodules per plant but root length and lateral roots were increased. Shoot and root characters were significantly associated under LP. There is sufficient genetic variability among groundnut genotypes for LP and this variability is mainly visible during pegging stage.